The rationale for liquid biopsy in colorectal cancer: a focus on circulating tumor cells. (September 2015) - Gazzaniga, Paola; Raimondi, Cristina; Nicolazzo, Chiara; Carletti, Raffaella; di Gioia, Cira; Gradilone, Angela; Cortesi, Enrico
<x xml:space="preserve">Abstract</x> Capturing circulating tumor cells (CTCs) and/or circulating tumor DNA from blood, which represents a precious source of biological material derived from both primary and metastatic tumors, has been named a 'liquid biopsy'. While the circulating tumor DNA might be more representative of the bulk of the metastatic tumor, CTCs are thought to reflect more of the metastases-initiating cells. Consequently, a liquid biopsy made of tumor cells and tumor DNA that is able to track cancer evolution, as a fingerprint of the patient's individual tumor, and is easy to perform at every stage of the disease course, sounds attractive. This article mainly focuses on the applications of CTCs to track tumor dynamics in real time using colorectal cancer as a model system. The analysis of viable CTCs at DNA, RNA and protein levels, as well as their expansion in vitro, may allow deep investigation of the features of metastases-initiating cells.